‘CUIUS REGIO EIUS RELIGIO?’ - ZJAZD HISTORYKÓW PAŃSTWA I PRAWA, LUBLIN 22-24 WRZEŚNIA 2006 ROKU - Loska, Elżbieta (Zeszyty Prawnicze, 2017)
‘CUIUS REGIO EIUS RELIGIO?’ - ZJAZD HISTORYKÓW PAŃSTWA I PRAWA, LUBLIN 22-24 WRZEŚNIA 2006 ROKU